Improving the Stability and Activity of Arginine Decarboxylase at Alkaline pH for the Production of Agmatine - Hong, Eun Young; Lee, Sun-Gu; Yun, Hyungdon; Kim, Byung-Gee (Frontiers in Catalysis, 2021)
Agmatine, involved in various modulatory actions in cellular mechanisms, is produced from arginine (Arg) by decarboxylation reaction using arginine decarboxylase (ADC, EC 4.1.1.19). The major obstacle of using wild-type Escherichia coli ADC (ADCes) in agmatine production is its sharp activity loss and instability at alkaline pH. Here, to overcome this problem, a new disulfide bond was rationally introduced in the decameric interface region of the enzyme. Among the mutants generated, W16C/D43C increased both thermostability and activity. The half-life (T1/2) of W16C/D43C at pH 8.0 and 60 ° C was 560 min, which was 280-fold longer than that of the wild-type, and the specific activity at pH 8.0 also increased 2.1-fold. Site-saturation mutagenesis was subsequently performed at the active site residues of ADCes using the disulfide-bond mutant (W16C/D43C) as a template. The best variant W16C/D43C/I258A displayed a 4.4-fold increase in the catalytic efficiency when compared with the wild-type. The final mutant (W16C/D43C/I258A) was successfully applied to in vitro synthesis of agmatine with an improved yield and productivity (> 89.0% yield based on 100 mM of Arg within 5 h).